2014
DOI: 10.1681/asn.2013030252
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β–Activated Kinase 1 Is Crucial in Podocyte Differentiation and Glomerular Capillary Formation

Abstract: TGF-b-activated kinase 1 (TAK1) is a key intermediate in signal transduction induced by TGF-b or inflammatory cytokines, such as TNF-a and IL-1, which are potent inducers of podocyte injury responses that lead to proteinuria and glomerulosclerosis. Nevertheless, little is known about the physiologic and pathologic roles of TAK1 in podocytes. To examine the in vivo role of TAK1, we generated podocyte-specific Tak1 knockout mice (Nphs2-Cre mice, Tak1 Δ/Δ mice exhibited impaired formation of podocyte foot process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 71 publications
0
11
0
1
Order By: Relevance
“…There is now evidence for ‘cross‐talk’ between podocytes and glomerular endothelial cells . We found that at 6 months after podocyte‐specific PTEN deletion, there was swelling of glomerular endothelial cells, followed by obliteration of some of the glomerular capillaries, suggesting that PTEN deletion in podocytes interrupts communication between podocytes and glomerular endothelial cells.…”
Section: Discussionmentioning
confidence: 69%
“…There is now evidence for ‘cross‐talk’ between podocytes and glomerular endothelial cells . We found that at 6 months after podocyte‐specific PTEN deletion, there was swelling of glomerular endothelial cells, followed by obliteration of some of the glomerular capillaries, suggesting that PTEN deletion in podocytes interrupts communication between podocytes and glomerular endothelial cells.…”
Section: Discussionmentioning
confidence: 69%
“…Data from in vitro studies indicate that TGF-␤1-stimulated collagen expression in mesangial cells is mediated via the TAK1/MKK3/p38 signaling cascade and fibronectin expression in fibroblasts (13,38,69). Moreover, investigations using pharmacological and genetic blockade in in vivo models of glomerular and tubulointerstitial injury in mice have shown that the TAK1/MKK3/p38 and JNK pathways promote renal fibrosis (13,39). Both p38 and JNK are downstream targets of TAK1 activation.…”
Section: Profibrotic Effects Of Tgf-␤1mentioning
confidence: 99%
“…Vegf-A expression in podocytes is in part dependent on the transcription factor LMX1B, leading to reduced VEGF production and decreased fenestration of endothelial cells in LMX1B deficient mice [57]. In contrast, the deletion of TGF-ˇ-activated kinase 1 (TAK1) in podocytes increases VEGF production causing abnormalities in glomerular and capillary formation [58]. Thus, the function of tightly balanced VEGF-A expression is indispensable for the development and maintenance of glomerular structure and function.…”
Section: Development Of the Glomerular Vasculaturementioning
confidence: 99%